Kriminalisasi Marital Rape: Eksistensi dan Pembuktiannya - Angeline Danica; Novita Aristyana; Charine Elsina Natalia Tahapary; Ramadhanis Samadi (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2022)
Abstract Generally, marriage is a moment of happiness, but it cannot deny that when marriage occurs, it brings misery in it such as Domestic Violence. There are several causes of Domestic Violence which split into various aspects, and one of them is sexual violence. This often makes the wife in a weak position or has a more inferior position, making her victim of her husband. The marital status that binds the wife as the victim and the husband as the perpetrator should not abolish the woman's rights over her body. The wife's position as a victim causes her physical and psychological traumatization, making the community also take responsibility by providing moral support. Not necessarily blaming the victim and justifying the behaviour of the perpetrator because it is still considered forbidden for the community to interfere in household matters. Any form of violence and its occurrence is not something that can be accepted and justified in the rule of law in each country. Therefore, the purpose of this paper is to discuss acts related to sexual harassment without the victim's consent even in a marriage bond, known as marital rape. In Indonesia, the criminal act of domestic violence is regulated in Act No. 23 of 2004, which concerns the elimination of domestic violence, requires a clear and firm implementation, because the law must provide protection to victims and the accountability of perpetrators of such violence must be adjusted to the applied laws and regulations.